2013
DOI: 10.15282/ijame.8.2013.34.0122
|View full text |Cite
|
Sign up to set email alerts
|

Vortex Tube Air Cooling: The Effect on Surface Roughness and Power Consumption in Dry Turning

Abstract: There has been increased awareness of the need to reduce environmental impacts in the last 10 years. The manufacturing industry is striving to reduce environmental impacts by introducing new materials with better characteristics, that consume less processing power and use smaller amounts of processing coolant. The main objective of this paper is to study the effect of the Ranque-Hilsch vortex cooling tube on power consumption and surface roughness quality in the turning process when machining mild steel materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Ancak Ekinović ve arkadaşları, ıslah çeliklerinde 60 m/dk kesme hızı, 0.098 mm/dev ilerleme, 0.5 mm kesme derinliği ile kuru kesme ve geleneksel soğutucu kullanımının, vorteks tüpü kullanımına göre kesme kuvvetlerine daha olumlu etki sağladığını belirtmişlerdir [33]. Ayrıca A36 alaşımının 160 m/dk sabit hızla ve değişken ilerleme ve kesme derinliklerinde tornalanmasında vorteks tüpü kullanımının, kuru kesmeye göre kesme sıcaklıklarını azaltırken güç tüketimini ve yüzey pürüzlülüğünü arttırdığını gözlemlemişlerdir [41]. Naumov ve arkadaşları, vorteks tüp ile soğutma ve yağlamanın aynı anda yapıldığı sistemlerin, yapı çeliğinde kesme işleminin temel özelliklerinin iyileştirilmesine ve takım ömrüne katkıda bulunduğunu belirtmişlerdir [37].…”
Section: şEkilunclassified
“…Ancak Ekinović ve arkadaşları, ıslah çeliklerinde 60 m/dk kesme hızı, 0.098 mm/dev ilerleme, 0.5 mm kesme derinliği ile kuru kesme ve geleneksel soğutucu kullanımının, vorteks tüpü kullanımına göre kesme kuvvetlerine daha olumlu etki sağladığını belirtmişlerdir [33]. Ayrıca A36 alaşımının 160 m/dk sabit hızla ve değişken ilerleme ve kesme derinliklerinde tornalanmasında vorteks tüpü kullanımının, kuru kesmeye göre kesme sıcaklıklarını azaltırken güç tüketimini ve yüzey pürüzlülüğünü arttırdığını gözlemlemişlerdir [41]. Naumov ve arkadaşları, vorteks tüp ile soğutma ve yağlamanın aynı anda yapıldığı sistemlerin, yapı çeliğinde kesme işleminin temel özelliklerinin iyileştirilmesine ve takım ömrüne katkıda bulunduğunu belirtmişlerdir [37].…”
Section: şEkilunclassified
“…The feed rate in turning process has a significant effect on surface roughness and power consumption. At higher feed rates the surface roughens increases affecting the quality of the components [18,19]. Authors have not found much work related to roller burnishing effect on surface roughness and microhardness in different conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Ginting et al [9] stated that the replacement of wet machining with RHVT cooling can save 80 cents apiece. Taha et al [10] studied the effect of RHVT cooling on surface roughness and power consumption in dry turning. The results showed that this cooling solution reduces the cutting temperature.…”
Section: Introductionmentioning
confidence: 99%